2006
DOI: 10.1007/s00441-006-0258-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of single articular chondrocytes

Abstract: Although previous studies in the field of tissue engineering have provided important information about articular cartilage, their conclusions are based on population averages and do not account for variations in cell subpopulations. To obtain a precise understanding of chondrocytes, we investigated the effects of cartilage zone and seeding duration on single chondrocyte gene expression to select an optimal zone for tissue engineering (Phase I), followed by an evaluation of growth factor exposure on the zone se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 42 publications
5
35
0
Order By: Relevance
“…Previous studies including our own have reported several differences between SZC and DZC Darling and Athanasiou, 2005a;Darling and Athanasiou, 2005b;Darling et al, 2004;Dowthwaite et al, 2004;Eleswarapu et al, 2006;Marles et al, 1991;Siczkowski and Watt, 1990;Stephens et al, 1992;Waldman et al, 2003;Zanetti et al, 1985). In the current study, we have identified BMP as an important factor in the differential capacities of SZC and DZC to accumulate matrix and to hypertrophy.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies including our own have reported several differences between SZC and DZC Darling and Athanasiou, 2005a;Darling and Athanasiou, 2005b;Darling et al, 2004;Dowthwaite et al, 2004;Eleswarapu et al, 2006;Marles et al, 1991;Siczkowski and Watt, 1990;Stephens et al, 1992;Waldman et al, 2003;Zanetti et al, 1985). In the current study, we have identified BMP as an important factor in the differential capacities of SZC and DZC to accumulate matrix and to hypertrophy.…”
Section: Discussionsupporting
confidence: 67%
“…The distinction is important as the use of BMPs and/or other growth factors in cell-based strategies for cartilage tissue engineering or regeneration cannot be optimized without specific knowledge about the potentially distinct effects of such factors on SZC versus DZC. Recent reports on the effects of other growth factors such as transforming growth factor β and insulin-like growth factor 1 indicate that chondrocyte sub-populations have zonespecific responses (Darling and Athanasiou, 2005a;Eleswarapu et al, 2006). In this study we compared morphology, gene expression, matrix accumulation and quality by SZC versus DZC in a scaffold-free in vitro model of cartilage-like tissue formation.…”
Section: Introductionmentioning
confidence: 99%
“…Specific primers for each gene were identified from the literature [37][38][39][40] and are listed in Table 1. Gene expression data were analyzed using a two-way analysis of variance (ANOVA), with a significance level of p < 0.05.…”
Section: Ddctmentioning
confidence: 99%
“…Moreover, human chondrocytes with high chondrogenic capacity were found to express markers associated with cell-cell or cell-matrix interactions, while a low capacity for matrix production was associated with higher expression of IGF-1 and catabolic genes, e.g., matrix metalloproteinases (37). In relation to the findings presented above, it is also important to note that articular cartilage chondrocytes differ in response to IGF-1 depending on the zone from which they were isolated (38).…”
Section: Discussionmentioning
confidence: 80%